1978
DOI: 10.1021/ic50181a039
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and structure of a ternary oxide of barium and rhenium, Ba3Re2-xO9

Abstract: Attempts to synthesize-BaRe03 resulted in formation of a slightly nonstoichiometric compound with the ideal formula Ba3Re209. It was found to have the space group R h with hexagonal unit cell parameters a = 5.7699 ( 5 ) A and c = 20.799 (2) A, Z = 3. A total of 2816 reflections were measured on an automatic diffractometer, and the structure was refined by full-matrix least squares on 308 unique reflections to a final R value of 0.027 and R, of 0.036. It consists of a nine-layer repeat sequence of hexagonal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In the current LaTi 1Àx O 3 case, the upper limit for g L of 5 = 12 for La 4 Ti 3 O 12 is set not by this rather steric limit but by the maximal allowed valence of Ti in charge balance considerations. In closely related phases, however, where ions of differing charge can apparently occupy the various cation sites (see [1] for examples) it may be possible to obtain a phase with a higher value for g L than 5 = 12 , and in fact the sequence and the g L value corresponding to x 1 = 3 has been observed [14].…”
Section: The Layer Model In Superspacementioning
confidence: 99%
“…In the current LaTi 1Àx O 3 case, the upper limit for g L of 5 = 12 for La 4 Ti 3 O 12 is set not by this rather steric limit but by the maximal allowed valence of Ti in charge balance considerations. In closely related phases, however, where ions of differing charge can apparently occupy the various cation sites (see [1] for examples) it may be possible to obtain a phase with a higher value for g L than 5 = 12 , and in fact the sequence and the g L value corresponding to x 1 = 3 has been observed [14].…”
Section: The Layer Model In Superspacementioning
confidence: 99%
“…Some compounds with the chemical formula A 3 &M 2 X 9 (& = vacancy) have a Ba 3 Re 2 O 9 -type structure, which is regarded as a layered perovskite structure (Calvo et al, 1977). The present authors have reported a barium tungstate, Ba 3 W 2 O 9 , with the Ba 3 Re 2 O 9 -type structure, which was prepared by a highpressure synthesis technique (Urushihara et al, 2017).…”
Section: Introductionmentioning
confidence: 76%
“…In the homologous series of these compounds, just like in the AB 2 C 2 (ThCr 2 Si 2 -and CaBe 2 Ge 2 -type) compounds series, the value of a parameter varies, as a rule, proportionally to variation of A, B and C atoms sizes. Furthermore, in [53], Nb [54 -56], Ta [57 -59], Re [60], Ru [61] and Ti [62] would be approximately equal to average bond lengths in В'О 6 octahedra of respective elements and fall into the range 1.90-2.00 Å (the limit of stability of B'-O bonds in these elements octahedra is rather wide (1.70-2.30 Å)). Therefore, the elementary unit parameter a and the distances B-B or C-C in the B 2 C 2 -sandwich internal plane would be in the range 3.80-4.00 Å and 2.76-2.83 Å, respectively.…”
Section: Candidate Superconductor Compoundsmentioning
confidence: 99%